PENGARUH DESAIN LIVERY BUS TERHADAP KEPUASAN KONSUMEN PERUSAHAAN BUS AKAP JURUSAN JAKARTA-WONOSOBO (STUDI KASUS: PO. SINAR JAYA, PO. DAMRI, PO. ROSALIA INDAH, PO. KUPU KUPU AYU): THE INFLUENCE OF BUS LIVERY DESIGN ON CUSTOMER SATISFACTION OF AKAP BUS COMPANY MAJORING IN JAKARTA-WONOSOBO (CASE STUDY: PO. RAY JAYA, PO. DAMRI, PO. ROSALIA INDAH, PO. KUPU KUPU AYU) - Widi Reza Prasetya; Drajatno Widi Utomo; Achmad Syarief (Universitas Trisakti, 2024)
Based on a survey conducted by the Ministry of Transportation's Balitbang in 2022, buses are the mode of public transportation most used by travelers with a total of 14.1 million. Along with the large number of passengers, the number of buses continues to increase every year. The large number of buses means that each company must have its own characteristics, one of which is its livery design. Livery is a pattern or design on the bus body to symbolize the identity of the bus company. To attract interest and create consumer satisfaction. On this basis, this research aims to find out how much influence bus livery design has on customer satisfaction with the AKAP bus company and to identify which bus livery design elements best suit consumer perceptions. This research uses quantitative methods. The results of this research show that livery design has a significant influence on consumer satisfaction, although not dominant (53.5:46.5). Perceptually, this research obtained data that the bus livery design element in the form of color is the element that best suits consumer perceptions.